Knowledge, attitudes, and practices regarding the prevention of patient falls among registered nurses in a private hospital in Malaysia - Keetha Aramo; Annamma Kunjukunju; Nurul Fariza Mohd Mustafa (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Falls are the second leading cause of accidental injury and non -intentional deaths worldwide, according to World Health Organization (WHO). Purpose: To identify knowledge, attitude and practices on preventing patient fall among Registered Nurses of a Private Hospital. Method: A quantitative non-experimental cross-sectional study was chosen as the research design. The questionnaire used in this study was adapted from Cho and Jang (2020), and the knowledge test consists of 13 items as a questionnaire adapted from the Nursing clinical practice guidelines on preventing patient fall in hospitals by the ministry of health, Singapore. An online google form was distributed to a sample size of 132 Registered Nurses (Using Krejcie and Morgan Table (1970). For the study population, the researcher involved all the registered nurses working at private hospital with a total population of N=200. The data were analysed using IBM Statistical Package for Science (SPPS) Version. Participants’ knowledge, attitude and practices were analysed using frequencies, percentages, means, and standard deviations. Pearson’s correlation coefficients were calculated for the relationships between knowledge, attitudes, and practices in fall-prevention activities. Results: The majority of registered nurses in private hospital have good knowledge on patient fall prevention. Conclusion: The study suggested multifaceted implementation programs for fall prevention should be implemented to strengthen their positivity in knowledge, attitude and practice.